National Trends in Disease Activity for COVID-19 Among Children in the US - Hutch, Meghan R.; Liu, Molei; Avillach, Paul; , Consortium for Clinical Characterization of COVID-19 by EHR (4CE); Luo, Yuan; Bourgeois, Florence T. (Frontiers in Pediatrics, 2021)
Ongoing monitoring of COVID-19 disease burden in children will help inform mitigation strategies and guide pediatric vaccination programs. Leveraging a national, comprehensive dataset, we sought to quantify and compare disease burden and trends in hospitalizations for children and adults in the US.